Coordinated regulation of acid resistance in Escherichia coli. Issue 1 (December 2017) - Aquino, Patricia; Honda, Brent; Jaini, Suma; Lyubetskaya, Anna; Hosur, Krutika; Chiu, Joanna; Ekladious, Iriny; Hu, Dongjian; Jin, Lin; Sayeg, Marianna; Stettner, Arion; Wang, Julia; et al.
Abstract Background EntericEscherichia coli survives the highly acidic environment of the stomach through multiple acid resistance (AR) mechanisms. The most effective system, AR2, decarboxylates externally-derived glutamate to remove cytoplasmic protons and excrete GABA. The first described system, AR1, does not require an external amino acid. Its mechanism has not been determined. The regulation of the multiple AR systems and their coordination with broader cellular metabolism has not been fully explored. Results We utilized a combination of ChIP-Seq and gene expression analysis to experimentally map the regulatory interactions of four TFs:nac, ntrC, ompR, andcsiR . Our data identified all previouslyin vivo confirmed direct interactions and revealed several others previously inferred from gene expression data. Our data demonstrate thatnac andcsiR directly modulate AR, and leads to a regulatory network model in which all four TFs participate in coordinating acid resistance, glutamate metabolism, and nitrogen metabolism. This model predicts a novel mechanism for AR1 by which the decarboxylation enzymes of AR2 are used with internally derived glutamate. This hypothesis makes several testable predictions that we confirmed experimentally. Conclusions Our data suggest that the regulatory network underlying AR is complex and deeply interconnected with the regulation of GABA and glutamate metabolism, nitrogen metabolism. These connections underlie and experimentally validated model of AR1 in which the decarboxylation enzymes of AR2 are used with internally derived glutamate.